Mechanical properties and seismic behavior of confined masonry walls in freeze-thaw environment. (June 2021) - Zhou, Yan; Zheng, Shansuo; Chen, Liuzhuo; Long, Li; Dong, Liguo
Abstract: Previous literatures show that freeze-thaw cycles (FTC) will deteriorate the physical and mechanical properties of masonry materials. The research in this paper focused on the influence of FTC on mechanical properties and seismic performance of confined masonry walls. A series of mortar cubes, brick units and double-shear specimens built of concrete brick and three types of mortar (cement, cement-lime and cement-fly ash) were subjected to testing after rapid freeze-thaw experiment in environmental chamber. Besides, quasi-static tests were performed on four confined masonry wall specimens to investigate their seismic behavior under varying degrees of freeze-thaw damage. The test results indicated that as the number of FTC increased, the compressive strength of mortar and bricks, masonry shear bond strength, load-carrying capacity, displacement ductility, secant stiffness and energy dissipation capacity of confined masonry walls all shown a downward trend. In addition, a prediction model was proposed to obtain the degradation of shear bond strength of masonry subjected to freeze-thaw damage, and could be used in the rapid investigation and non-destructive detection. Moreover, the addition of fly ash was helpful to slow down the deterioration of masonry buildings in freeze-thaw environment.